2021
DOI: 10.1016/j.nicl.2021.102854
|View full text |Cite
|
Sign up to set email alerts
|

ALL-Net: Anatomical information lesion-wise loss function integrated into neural network for multiple sclerosis lesion segmentation

Abstract: Highlights A new algorithm, ALL-Net, is introduced to improve MS lesion segmentation. ALL-Net integrates anatomical coordinate information into the neural network. ALL-Net integrates lesion-wise loss function to improve small lesion detection. ALL-Net is robust to both small- and large-scale MS lesion datasets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…43 To minimize effects of this undesired variation, future in vivo validation should include automated lesion segmentation techniques. [44][45][46][47] Nevertheless, our data suggest that our approximation produces a good qualitative agreement with independent measurements of iron and myelin within MS lesions. for specific quantitative mapping of myelin 49,50 and laser ablation inductively coupled plasma mass spectroscopy for iron quantitative mapping.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…43 To minimize effects of this undesired variation, future in vivo validation should include automated lesion segmentation techniques. [44][45][46][47] Nevertheless, our data suggest that our approximation produces a good qualitative agreement with independent measurements of iron and myelin within MS lesions. for specific quantitative mapping of myelin 49,50 and laser ablation inductively coupled plasma mass spectroscopy for iron quantitative mapping.…”
Section: Resultssupporting
confidence: 73%
“…In the present study, lesion segmentation for correlation analysis was performed manually on T2 FLAIR images, an approach prone to intra‐ and interreader variability 43 . To minimize effects of this undesired variation, future in vivo validation should include automated lesion segmentation techniques 44–47 . Nevertheless, our data suggest that our approximation produces a good qualitative agreement with independent measurements of iron and myelin within MS lesions.…”
Section: Discussionmentioning
confidence: 85%
“…2). Future work involves pairing QSMRim-Net with an automated T2-FLAIR lesion segmentation algorithm, such as All-Net [21] with geometric loss [54] and attention-based approaches [55] [56], followed by an automated method to separate confluents lesions [57]. We plan to adapt and train the algorithm to work directly on T2-FLAIR lesion segmentations.…”
Section: Discussionmentioning
confidence: 99%
“…In studies of chronic active MS lesions on MRI, lesions are typically identified on the T2-weighted-Fluid-Attenuated Inversion Recovery (T2-FLAIR) image and then are determined to be chronic active through visual inspection on susceptibility imaging. This process is time consuming and prone to inter- and intra-rater variability [20, 21]. For these lesions to be further studied at a large scale and translated into clinical practice, there is a great need for automated methods to identify chronic active MS lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Convolutional neural networks (CNNs) have been the dominant approach across a variety of medical image computing applications such as magnetic resonance imaging (MRI) reconstruction [Zhang et al, 2020c;Zhang et al, 2021b], brain lesion segmentation [Zhang et al, 2021a;Zhang et al, 2019a], disease identification [Khosla et al, 2019;Zhang et al, 2022], and low-dose CT denoising Fan et al, 2019]. Two main properties [Elsayed et al, 2020] of CNNs are believed to be the key to their success: 1) The local receptive field increases as the network goes deeper [Huang et al, 2017;He et al, 2016], providing richer contextual information for down-stream tasks; 2) Spatially invariant convolution filters regularize the network training, serving as a good inductive bias for grid-based image data [Simoncelli and Olshausen, 2001].…”
Section: Introductionmentioning
confidence: 99%